THE ROLE OF ESG IN MODERATING THE RELATIONSHIP OF FINANCIAL PERFORMANCE TO MARKET REACTIONS - Reni Sartika Dewi; Suripto; Holiawati (ZILLZELL MEDIA PRIMA, 2025)
This study aims to analyze the role of ESG (Environmental, Social, and Governance) in moderating the relationship between financial performance and market reactions in companies listed on the Indonesia Stock Exchange (IDX). Using a quantitative associative approach, this research analyzes panel data from 57 companies over the 2019–2023 period (285 firm-year observations). Financial performance was measured by Earnings Per Share (EPS), market reaction by year-end closing stock price, and ESG performance using scores from the Bloomberg Terminal. Panel data regression analysis results show that financial performance (EPS) has a positive and significant effect on market reaction. However, contrary to the hypotheses, all three ESG dimensions (Environmental, Social, and Governance) did not show a significant moderating effect on this relationship. These findings indicate that investors in the Indonesian capital market still rely on traditional financial metrics as the primary drivers of investment decisions and have not yet fully integrated sustainability performance considerations into their valuation models. The study's implications highlight the need for better ESG education and increased investor awareness to encourage more sustainable investment practices in emerging markets.